Acetylcholinesterase activity in Toxoplasma gondii tachyzoites (RH strain) - Tonin A.A. (2015)
© 2014, Springer-Verlag London.This study aimed to investigate acetylcholinesterase (AChE) presence and its enzymatic activity in Toxoplasma gondii (RH strain) tachyzoites and to test a well-known inhibitor of this enzyme. Tachyzoites were obtained from cell culture (sample 1) and peritoneal fluid of experimentally infected mice (sample 2). The protein concentration was determined for each pellet of tachyzoite. In this study, our hypothesis is that T. gondii has the enzyme AChE just like other parasites, and this knowledge might be helpful to develop new chemotherapy strategies to fight toxoplasmosis. The AChE activity was detected in the parasite using 0.025, 0.05, 0.1, 0.2, 0.4, 0.7, and 1.0 mg mL−1 concentrations of protein from tachyzoites. AChE activity has increased progressively according to protein increase, up to a certain point, when it had reduced activity when higher concentrations of protein were tested. The AChE activity of T. gondii was also inhibited with the use of trichlorfon, similar to what occurs with other parasites. Based on these results, we conclude that the enzyme AChE is present in T. gondii tachyzoites. Trichlorfon is able to inhibit the enzyme detected in this study, which might become an option for chemotherapy.